Use of Capnography During Resuscitation of Patients in Intensive Care Units - Mosaab Farajallah MSN; Ahmad Ayed PhD; Ahmad Batran PhD; Moath Abu Ejheisheh PhD; Bahaa Alassoud PhD; Bahaaeddin M. Hammad PhD; Mohammed F. Hayek PhD; Ahmed Batran MSN (SAGE Open Nursing)
Introduction Cardiac arrest is a serious threat to patients in intensive care units (ICUs), posing a significant risk that can lead to a patient's death if not treated promptly. The utilization of capnography to improve outcomes for patients with cardiac arrest has received substantial attention in research. Purpose The purpose of this study was to assess ICU nurses’ knowledge and perceptions of capnography use specifically during cardiac arrest resuscitation in South West Bank Hospitals. Methods A cross-sectional descriptive approach was used, employing a questionnaire for data collection. Data were collected from January 15, 2024, to March 15, 2024. The sample of the study consists of 155 nurses working in ICUs in South West Bank hospitals. Results The results of the study revealed that most participants ( N = 106, 68.4%) had low knowledge of capnography, with a mean knowledge score of 52.9 ± 15.3. The results also showed that the participants’ perception of capnography use was fair in N = 60 (38.7%) and poor in N = 59 (38.1% ) . Furthermore, the results revealed that there were no significant differences in capnography knowledge based on selected demographic and professional characteristics of nurses (p > 0.05), indicating consistent knowledge gaps across experience levels. Conclusion The study confirmed that ICU nurses had fair and poor perceptions toward capnography use during cardiac arrest resuscitation. This highlights the need for targeted education to improve bedside capnography assessment skills among ICU nurses. Recommendations for enhancing capnography training and further research were presented.